2017
DOI: 10.1007/s00262-017-1980-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic acids from Staphylococcus aureus stimulate proliferation of human non-small-cell lung cancer cells in vitro

Abstract: Pulmonary infections are frequent complications in lung cancer and may worsen its outcome and survival. Inflammatory mediators are suspected to promote tumor growth in non-small-cell lung cancer (NSCLC). Hence, bacterial pathogens may affect lung cancer growth by activation of inflammatory signalling. Against this background, we investigated the effect of purified lipoteichoic acids (LTA) of Staphylococcus aureus (S. aureus) on cellular proliferation and liberation of interleukin (IL)-8 in the NSCLC cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 60 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…Growing evidence has indicated that bacterial infection is highly associated with certain human malignancies ( 23 ). It has been reported that lipoteichoic acids from S. aureus induce proliferation of two human non-small-cell lung cancer cell lines, A549 and H226 ( 24 ). However, the role of S. aureus infection in ccRCC still remains to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has indicated that bacterial infection is highly associated with certain human malignancies ( 23 ). It has been reported that lipoteichoic acids from S. aureus induce proliferation of two human non-small-cell lung cancer cell lines, A549 and H226 ( 24 ). However, the role of S. aureus infection in ccRCC still remains to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time-reactions were performed as described before [ 64 ]. The mRNA expressions were expressed as –ΔCt value (Ct value gene of interest – Ct value gene of reference gene [PBGD]).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that TLR-2 forms a complex with CD36 following stimulation by S. aureus LTA. LTA actively participates in bacterial invasion of host cells via contact with host cell receptor CD36, TLR-2, and TLR-2/6 and TLR-2/1 heterodimers, leading to host immune response, such as pathogen phagocytosis and cytokine production (4,7,8,10,24,25).…”
Section: Discussionmentioning
confidence: 99%